Peran sertifikasi halal pada UMKM dalam memperkuat ekonomi syariah di Indonesia - Amellya Yunita Syari; Hanna Albinia Imtinan; Gina Mutiara Yasmin; Fadhli Suko Wiryanto (Nur Science Institute, 2025)
This study explores the role of halal certification in strengthening the Islamic economy in Indonesia, a country with the world's largest Muslim population. Using a qualitative approach, the research examines the state of Islamic economic growth and the strategic impact of halal certification on MSMEs. The findings suggest that halal certification enhances the competitiveness of local products in the global market by improving product quality and fostering consumer trust. Additionally, halal certification supports the development of a sustainable Islamic economic ecosystem, particularly in the food and beverage sector, which serves as a key driver of growth. However, challenges in implementing certification, such as the lack of understanding among MSMEs regarding procedures and the importance of halal certification, remain significant obstacles. Regulatory support, such as Law Number 33 of 2014, has accelerated the adoption of halal certification. This study concludes that halal certification is a crucial element in optimizing Indonesia's Islamic economic potential and provides strategic recommendations to increase MSME participation in the global halal ecosystem.